Assessment of Antimicrobial Consumption in Multi-Field Hospitals with Pediatric Inpatients: Conventional vs. Novel Pediatric-Adjusted Methodologies - Svetlana Rachina; Yuliya Belkova; Roman Kozlov; Vladimir Mladov; Vladimir Mishchenko; Alla Andreeva; Olga Domanskaya; Ulyana Portnjagina; Anastasiia Dushina; Khadizhat Zainalabidova (MDPI AG, 2023)
Background: the objective of this study was to propose a methodology for the assessment of antimicrobial consumption (AMC) in pediatric inpatients and to estimate variances in consumption levels in multi-field hospitals with pediatric inpatients, calculated by means of the pediatric-adjusted methodology vs. the conventional methodology. Methods: the pediatric-adjusted methodology based on the conventional ATC/DDD method and children's DDDs (cDDD) for antimicrobials were proposed and validated in a series of probabilistic sensitivity analyses of real clinical data extracted from the receipt notes of three multi-field hospitals. Differences in AMC in multi-field hospitals with pediatric inpatients, calculated by means of the proposed methodology vs. the conventional methodology, were assessed for a virtual cohort of inpatients, with the pediatric share increasing by 1%. Results: in children ≤12 years old, assessment by the standard methodology resulted in a 59% underestimation of AMC from the levels based on prescribed doses, vs. a 25% underestimation for the proposed methodology. In a mixed-age virtual population of inpatients, the underestimation of consumption levels rose to 321% for the ATC/DDD methodology compared to the proposed one. Conclusions: the proposed methodology demonstrated a higher accuracy of AMC estimates compared to the conventional one and can be considered for the quantification of antimicrobial utilization in pediatric institutions and multi-field hospitals with a substantial share of pediatric inpatients.